Pengaruh Promosi, Harga dan Kualitas Layanan Terhadap Keputusan Pembelian Thrifting di Toko Second Barkley Malang - Asrafuddin, Asrafuddin; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research is conducted with the aim of investigating how price factors, promotional activities, and the quality of service impact consumers' choices when making purchases. The research methodology employed in this study is quantitative, involving the collection of data through the distribution of questionnaires to 80 respondents, specifically individuals who have either already purchased or intend to purchase second-hand clothing products online from Barkley Malang. Subsequently, the gathered data is processed using the SPSS application. Prior to analysis, the data is meticulously assessed for validity and reliability. The research then proceeds with classical assumption testing, multiple linear regression analysis, hypothesis testing, and a coefficient of determination examination. The variables under consideration in this study encompass promotional factors, pricing, and service quality as independent variables, while the dependent variable is the purchasing decision. The outcomes of this research reveal that promotion, pricing, and service quality all wield a significant influence on purchasing decisions, both individually and when considered collectively. Keywords: Purchase Decision, Promotion, Price And Service Quality